Bispectral Index Versus Minimum Alveolar Concentration Guided Anesthesia for Assessment of Intraoperative Awareness in Patients Undegoing Laparascopic Abdominal Surgery - Shreya Garg; Vinod Bala Dhir; Jyoti Gupta; Yadav, Rupesh; Deepak Verma (Indonesian Journal of Anesthesiology and Reanimation, 2025)
Introduction: Intraoperative awareness with explicit recall (AWR) occurs when an individual retains memory of intraoperative events after completion of anesthesia. It is an unpleasant feeling feared by both the patients and the anesthetists. Objective: This research aims to compare Bispectral Index (BIS) versus Minimum Alveolar Concentration (MAC) guided anesthesia for assessment of intra-operative awareness in patients undergoing laparoscopic abdominal surgery. Methods: This research is a prospective comparison involving 100 patients divided into two groups of 50 patients each. Group M (MAC): Desflurane concentration was maintained at a MAC value of 1. The BIS monitor was not to be applied to this group of patients at the time of induction, but in Group B (BIS), the BIS electrode was applied on the forehead immediately before induction. Hemodynamic parameters including heart rate and mean arterial blood pressure were recorded.  After the surgery, the patients were interviewed using the Modified Brice Awareness Questionnaire and Michigan Awareness Classification score for assessment of intra-operative awareness or consciousness at two intervals: in the post-anesthesia care unit and 48 hours after surgery. Results: Demographic data were comparable between groups M and B. No significant differences in the hemodynamic parameters, which include heart rate and mean arterial blood pressure (MAP) between the M group and the B group (p value>0.05). The patient’s awareness was compared based on a modified Brice awareness questionnaire. The distribution of awareness was comparable between groups M and B (0% vs. 4% respectively) (p value=0.495). The distribution of Michigan awareness classification scores was comparable between groups M and B. Class 0 (no awareness) was 98% vs. 96% respectively, and Class 1(isolated auditory perception) of 2% vs. 4% respectively with (p value=1). Conclusion: This research found that BIS-guided anesthesia works just as well as MAC-guided anesthesia at keeping patients from waking up and keeping an eye on changes in their blood pressure while they are under general anesthesia for laparoscopic abdominal surgery.